Bile duct abnormalities in secondary liver tumors - Davidenko, Nicolás; Casanova de Davidenko, Marys; Baldizán, Jorge; Davidenko, Antonio; Ripoll, Roberto; Grazziani, Yolanda (Cirugía del Uruguay, 1979)
The study comprised 15 cholangiograms of secondary growths in liver, obtained in 7 patients by intra or post - operatory cholangiography; 3 of them showed hilar compression which gave them a distinct aspect; in the 4 remaining cases cholangiography contributed little to available data, with the exception of one case. The 8 remaining cases corresponded to postmortem specimens. Injected minium made possible a comptete radiologic and histoiogic study, indicating various cholangiographic aspects such as infiltration, compression, stricture, dilatation, displacement and necrosis of biliary tract and, in particular, the existence of neocholangiogenesis at the level of secondary tumoral nade, a characteristic which does not appear elsewhere in bibliography.